THE CORRELATION BETWEEN STUDENTS’ HABIT IN LISTENING ENGLISH SONGS AND LISTENING COMPREHENSION - Vinni Septaviani; Nurdin; Andi Muhammad Dakhalan (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2023)
Students in Indonesia need the motivation to be more interested in English lessons, one of which is by giving songs in class. The English song can attract the students in the teaching and learning process for English class. The students at SMAN 1 Palu have a low ability in listening comprehension. This research aims to find out the relationship between the students’ habits in listening to English songs and their listening comprehension achievement. The result of this research consists of the interpretation of data obtained in this research, the relation of data obtained with the theories from both variables, and the relation comparison of this research with the previous students. The result data was obtained from 20 students of eleventh grade at MAN 1 Palu. Based on the result, the scores of sig between the effect Like Song and Don’t Like Song were 0,231 or more than 0,05. Then the researcher concluded that Listening to English song habits has a correlation with listening comprehension of the eleventh-grade students of MAN 1 Palu revealed by the mean score of the students’ questionnaire. The mean score level was 48.40%, which is a high category level.